The efficacy and safety of CDK4/6 inhibitors combined with endocrine therapy versus endocrine therapy alone in the adjuvant treatment of patients with high-risk invasive HR+/HER2-early breast cancer: A comprehensive updated meta-analysis of randomized clinical trials - Merve Keskinkilic; Mehmet Emin Arayici; Yasemin Basbinar; Hulya Ellidokuz; Tugba Yavuzsen; Ilhan Oztop (Breast)
Background: This paper aimed to evaluate the effectiveness of incorporating CDK 4/6 inhibitors (CDK4/6i) into ET for the adjuvant treatment of HR + HER2-resected early-stage breast cancer (ESBC) patients, employing meta-analysis. Methods: In this paper, we compiled randomized clinical trials focusing on CDK4/6i used in the adjuvant treatment of high-risk invasive HR-positive and HER2-ESBC patients. A meta-analysis was performed in line with the PRISMA guidelines. Results: We identified four clinical trials that met our inclusion criteria and were published between 2020 and 2024. These trials involved a combined sample size of 17,749 patients diagnosed with breast cancer. The data obtained from the pooled analysis revealed a remarkable beneficial trend in terms of invasive disease-free survival (iDFS) for the use of ET in combination with CDK4/6i compared to the group receiving ET alone (HR = 0.81, 95 % CI: 0.67–0.98, p = 0.03). Of note, CDK4/6 inhibitors demonstrated a notably beneficial effect in both grade 2 (HR = 0.69, 95 % CI: 0.59–0.81, p < 0.001) and grade 3 (HR = 0.76, 95 % CI: 0.65–0.89, p < 0.001). Significant improvements were noted in terms of distant relapse-free survival (dRFS) in the groups treated with abemaciclib and ribociclib (HR = 0.65, 95 % CI: 0.56–0.76, p < 0.001; HR = 0.72, 95 % CI: 0.58–0.89, p = 0.003, respectively). CDK4/6i didn't yield a statistically significant difference in overall survival (OS) (HR = 0.96, 95 % CI: 0.77–1.19, p = 0.69). The use of CDK4/6i with ET was associated with an increased risk of adverse events, particularly anemia and neutropenia, compared with ET alone (OR = 9.12, 95 % CI = 5.04–16.48, p < 0.001). Conclusion: The findings of this paper demonstrate a significant improvement in iDFS when ET is combined with CDK4/6i, compared to ET alone. Specifically, treatments with abemaciclib and ribociclib showed notable enhancements in dRFS.